Federated States of Micronesia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Federated States of Micronesia. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Federated States of Micronesia (FSM) highlights that the economy has performed well in recent years, with relatively high growth and low inflation. Fiscal and current account balances have recorded large surpluses since 2017, owing to the authorities' decision to save revenue windfalls. Nonetheless, the FSM faces significant medium-term uncertainty as various economic supports under the Compact Agreement with the United States are set to expire in 2023. Unless they are renewed, the FSM is expected to lose access to Compact grants, giving rise to a fiscal cliff in 2023; banking sector oversight by the Federal Deposit Insurance Corporation; and post-disaster rehabilitation assistance. The country is highly vulnerable to climate change, while private sector activity remains anaemic. It is recommended to improve resilience to climate change by strengthening capacity to implement adaptation projects. Over the medium term, disaster risks should be mitigated by using disaster insurance and disaster-contingent foreign financing.